Implikasi Legal Market Power Assessment dalam Big Data pada Era Ekonomi Digital - Stefanus (Jurnal Persaingan Usaha, 2023)
The development of information and technology in the world of law has occurred since the digitalization era has also developed. In Indonesia itself, this development began with regulations regarding telecommunications to the latest regarding personal data protection. So far, regulations in Indonesia appear to be standing alone without any legal umbrella, although some legal experts have mentioned the Electronic Information and Transaction Law as a semi-legal umbrella for regulating digitalization in Indonesia. The inclusion of digitization elements in the form of Big Data as well as technology often creates a new disturbance for the enforcement of business competition law in Indonesia which we often know is difficult to prove legally, this can be seen from the existence of economics as one of the sciences that assists in the application business competition law, with the inclusion of Big Data a new science emerges which seems to need to be of concern to the Commission for the Supervision of Business Competition in implementing technical regulations related to the Law on the Prohibition of Monopolistic Practices and Unfair Business Competition in Indonesia. Keywords: Big Data, Business Competition Law, and Digital Economy.